Meningkatkan kemampuan berbicara Bahasa Inggris anak melalui cerita bergambar - Wirhayati Wirhayati; Erni Susanti Nainggolan; Anita Sari; May Triranto Maharini (Altruis: Journal of Community Services, 2022)
In learning English, speaking aspect has an important role when communicating. The development of children's language skills underlies the ability to read. Tthe more they read, the easier it will be for children to understand writing, and the more fluent their speaking skills will be. However, in developing their English speaking, children have difficulty because of the limited vocabulary. Heving difficulty in expressing ideas and lack of courage to speak because they are afraid of being wrong are factors that prevent children from speaking English well. In addition to the factors mentioned above, internal factors, such as the lack of seriousness of children in learning English itself as well as inadequate learning methods and lack of media are obstacles for children in learning English. This is felt by the children of TPA RT 004/RW 04 Pabuaran Tumpeng Tangerang. The low interest in reading in the environment where they live is the basis for the lack of development of language skills, especially English. Therefore, the Community Service team (PKM) Universitas Pamulang (UNPAM) offers a problem solution in the form of teaching English with the method of storytelling by using digital media with illustrated stories in English. From the results of the PKM activities at Taman Alquran Pabuaran Tumpeng with a series of activities, it seems that the children are happy, interested, and active. If proves that the use of storytelling method through pictures can improve children's English speaking skills.